Genetic and pharmacological tools to study the role of discoidin domain receptors in kidney disease - Borza, Corina M.; Bolas, Gema; Pozzi, Ambra (Frontiers in Pharmacology, 2022)
Following injury the kidney undergoes a repair process, which results in replacement of the injured tissue with little evidence of damage. However, repetitive injuries or inability of the kidney to stop the repair process result in abnormal deposition of extracellular matrix (ECM) components leading to fibrosis and organ dysfunction. The synthesis/degradation of ECM components is finely regulated by several factors, including discoidin domain receptors (DDRs). These are receptor tyrosine kinases that are activated by collagens. Upon activation, DDRs control several cell functions that, when exacerbated, contribute to kidney injury and fibrosis. DDRs are undetectable in healthy kidney, but become rapidly upregulated in several kidney fibrotic conditions, thus making them attractive anti-fibrotic targets. DDRs contribute to kidney injury and fibrosis by promoting apoptosis of injured kidney cells, stimulating the production of pro-inflammatory cytokines, and regulating the production of ECM components. They achieve these effects by activating canonical intracellular molecules or by directly interacting with nuclear chromatin and promoting the transcription of pro-fibrotic genes. The goal of this review is to highlight canonical and non-canonical mechanisms whereby DDRs contribute to kidney injury/fibrosis. This review will summarize key findings obtained using cells and mice lacking DDRs and it will discuss the discovery and development of targeted DDR small molecule- and antisense-based inhibitors. Understanding the molecular mechanisms whereby DDRs control kidney injury and fibrosis might enable us to not only develop more selective and potent inhibitors, but to also determine when DDR inhibition needs to be achieved to prevent and/or halt the development of kidney fibrosis.